Inovasi Media Pembelajaran Berbasis Literasi Ekologi untuk Mengembangkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Noviyanti Noviyanti; Yeri Sutopo; Agus Yuwono (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to develop teaching materials in the form of picture storybooks based on ecological literacy to improve critical thinking skills of elementary school students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). This research is motivated by the lack of innovative learning media that can connect ecological issues with Natural and Social Sciences (IPAS) learning. The research subjects were 50 fifth-grade students at Al Ikhlas Islamic Elementary School who were divided into an experimental group and a control group. The validation process involved five media experts and five material experts, while the practicality test involved 15 teachers and 25 students. The validation results showed that the picture storybook obtained the